Pengaruh Influencer Leonardo Edwin terhadap Keputusan Berdonasi Generasi Z di Platform Kitabisa - Ivana, Michelle Javiera; Herawati, Netty; Lukitowati, Suci (Calathu: Jurnal Ilmu Komunikasi, 2023)
This study aimed to discover the influence of influencer Leonardo Edwin on the donation decisions of Generation Z on the Kitabisa crowdfunding platform. This study used an associative quantitative research design using the questionnaire method for data collection. This study used influencer theory and A-A procedure theory. This research examines the influence of the influencer variable (X) on the donation decision variable (Y) by testing a sample data of 100 individuals who are followers of the Instagram account @leo_edw. This study examined the influence of the influencer variable (X) on the donation decision variable (Y) by testing a sample data of 100 individuals who are followers of the Instagram account @leo_edw. The sampling technique used was simple random sampling. The obtained data was then processed using simple linear regression analysis using SPSS version 26 as the data processing tool. The results of this study showed that the value tcalculated (4.952) > ttable (1.984) at a 5% significance level for the sample of 100 respondents. Therefore, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. This indicated that there was an influence of the influencer variable (X) on the donation decision variable (Y). The coefficient value of the simple linear regression equation was determined to be 0.819. This meant that a 1% increase in the influencer variable would result in a 0.819 increase in the donation decision variable. Moreover, the influencer variable contributed significantly to the donation decision, with a contribution value of 0.200, or 20%. The remaining 80% was influenced by other variables not examined in this study. Keywords: influencer, donation decision, Kitabisa, generation Z, quantitative